Maneuvering Colonial and Postcolonial Resistances with Poetry: A Comparative Study of Nazrul and Walcott - Uddin, Md. Abu Saleh Nizam; Karim, Shah Mohammad Sanaul; Mahmud, Mohammad Riaz (Indonesian Journal of English Language Studies (IJELS), 2024)
This article aims to place poems by Kazi Nazrul Islam of Bangla literature in a comparative study with those by the Caribbean poet Derek Walcott. Nazrul wrote when his country India was under British colonial rule and Walcott wrote when his Caribbean region was under British colonialism and in postcolonial period. The study becomes inevitable against a backdrop where comparative studies of Nazrul have been conducted with American and European authors who lack similar colonial backgrounds. Additionally, when Nazrul is compared with non-American and non-European authors, his Islamic identity, which transforms into his all-embracing humanity, is often omitted or sidelined. Thus, when poems by Nazrul and those by Walcott are in a comparative study, the two poets from two different marginalized nations exhibit conspicuous affinities in their poetic resistances. This is how this paper looks forward to doing a comparative study of the poems by Nazrul and those by Walcott by adopting the methods of Traditional Literary Criticism and a new comparative study as shaped by Zepetnek. The results which the study yields are that the poets maneuver identical poetic resistances by addressing the nation’s unity, revival of history, composition of unique literature, concern for the working-class people, and anti-colonial struggle. The results of the research may contribute to raising cultural awareness among marginalized nations about resisting aggression.